Motivations and Incentives of Community Media Content Creators: A Case Study of SpodNás - Lucia Škripcová, (Communication Today, 2025)
Community media are a natural extension of the various lives of communities within this world. They serve as a platform for sharing content, ideas and views which the communities deem important. They are equally important to the content creator himself and the information recipient. The uniqueness of community content creation begins with the process of creating as such; as the authors are usually the same people as the recipients, the situation in question is very unlike the production processes we know from mass media. This case study aims to map one of the communities situated in the city of Trnava that calls itself SpodNás. It analyses the whole process of creating a zine and related community activities via participant observation of the content creation related to this community’s everyday life. The author also strives to define the boundaries whichdivide a passive and an active recipient, primarily through directly surveying the content creators themselves.